Censorship: Publish and Be Damned. Issue 1 (February 2014) - Coleman, Peter
State censorship in Australia has been rare, controversial and short-lived. There was almost none in the liberal nineteenth century. In the twentieth century, the two world wars, the Great Depression and the new age of terrorism led to more determined, if comparatively temporary, attempts to censor publications that advocated sedition or violence. Moral censorship of obscenity was also rare in the nineteenth century, but enjoyed an 'heroic' period following the arrival of a new realism in literature and the age of lurid comic books. The internet has made such censorship almost totally ineffective. Blaspheming the Christian religion is no longer treated as a punishable offence, although attacking Islam may still sometimes be deemed actionable in law. The advent of multiculturalism has encouraged legislation to restrict free speech deemed to be 'hate speech', but its application has been episodic, unpopular and ineffective. The contest between writers demanding freedom and censors demanding standards is unending. But at the moment, the balance favours writers.